Role of the systemic immune system in brain metastasis. - Hamilton, A; Sibson, N (2013)
Metastatic disease in the central nervous system (CNS) is a cause of increasing mortality amongst cancer patients. As with other types of cancer, cells of the systemic immune system play a range of important roles in the development of metastatic lesions in the CNS, both repressing and promoting tumour growth. Recent advances in immunotherapy have changed the emphasis in cancer treatment away from conventional chemotherapy and radiotherapy for certain tumour types. Despite this, our understanding of systemic immune system involvement in CNS metastases remains poor. The blood-brain barrier prevents the majority of diagnostic and therapeutic agents from crossing into the brain parenchyma until the late stages of metastatic disease. Thus, the development of immunotherapy for CNS pathologies is particularly desirable. This review draws together our current understanding in the relationships between CNS metastases and circulating systemic immune cells. We discuss the roles that circulating systemic immune cells may play in the homing of metastatic cells to the perivascular space, and the pro-metastatic and antagonistic roles that infiltrating systemic immune cells may play at sites of metastasis. This article is part of a Special Issue entitled 'Neuroinflammation in neurodegeneration and neurodysfunction'.